2003
DOI: 10.1097/01.ta.0000101067.52018.42
|View full text |Cite
|
Sign up to set email alerts
|

Changing Patterns in the Management of Penetrating Abdominal Trauma: The More Things Change, the More They Stay the Same

Abstract: Penetrating abdominal organ injury patterns and survival from PAI have remained similar over the past decade. Death from refractory hemorrhagic shock in the first 24 hours remains the most common cause of mortality. DCS and the open abdomen are being used more frequently with improved survival but result in significant morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
2
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(85 citation statements)
references
References 67 publications
3
73
2
7
Order By: Relevance
“…In a collective review of 1001 severely injured patients from 31 different reports, the survival rate was 50% (12). In a before-andafter comparison from Atlanta, the use of damage control increased from 7% to 18% and was associated with a decrease in mortality from 76% to 27% (13). A similar effect was noted from a study in Philadelphia where the mortality rate dropped from 42% to 10% (14).…”
Section: History Of Damage Control Surgerysupporting
confidence: 53%
See 1 more Smart Citation
“…In a collective review of 1001 severely injured patients from 31 different reports, the survival rate was 50% (12). In a before-andafter comparison from Atlanta, the use of damage control increased from 7% to 18% and was associated with a decrease in mortality from 76% to 27% (13). A similar effect was noted from a study in Philadelphia where the mortality rate dropped from 42% to 10% (14).…”
Section: History Of Damage Control Surgerysupporting
confidence: 53%
“…The rate of wound infection, abscess or fistula was 25% (15). In the previously mentioned studies from Atlanta and Philadelphia, an abscess was noted in 14% and 18%, and a fistula in 18% and 14%, respectively (13,14). In another study of 56 trauma patients with initial mortality rate of 27%, 31 patients required 58 subsequent operations for complications.…”
Section: History Of Damage Control Surgerymentioning
confidence: 99%
“…Studies have shown that most commonly affected hollow and solid organs after penetrating abdominal trauma are small intestines (30%) and liver (19%), respectively. [20][21][22] Colon (18%), stomach (13%), pancreas, and duodenum follow. [21,22] Bowel rupture following penetrating abdominal trauma lead to the gas and other intestinal ingredients leak into the peritoneum resulting in peritonitis.…”
Section: Discussionmentioning
confidence: 99%
“…8,[11][12][13] The time interval from injury to control of hemorrhage is the dominant variable defining patient survival. 8,[12][13][14][15] As a result, urban centres with advanced prehospital systems and experienced trauma surgeons (i.e., rapid decision-making) often show impressive survival characteristics despite major vascular injuries. [16][17][18][19] Given that patients with penetrating torso injuries behave much differently than those with blunt trauma, they should also be assessed using unique approaches.…”
Section: Initial Assessment and Resuscitationmentioning
confidence: 99%